The Effect of Financial Constraints on In-Group Bias: Evidence from Rice Farmers in Thailand - Suparee Boonmanunt; Stephan Meier (Institute of Labor Economics (IZA), 2020)
In-group bias can be detrimental for communities and economic development. We study the causal effect of financial constraints on in-group bias in prosocial behaviors – cooperation, norm enforcement, and sharing – among low-income rice farmers in rural Thailand, who cultivate and harvest rice once a year. We use a between-subjects design – randomly assigning participants to experiments either before harvest (more financially constrained) or after harvest. Farmers interacted with either in-group or out-group partners at village level. We find that in-group bias in cooperation and norm enforcement exist only after harvest, that is, when people are less financially constrained.
Keywords: C93; D64; D91; 330; cooperation; financial constraints; in-group bias; lab-in-the-field experiment; norm enforcement